(3EfYcGS GdfTGW GdHOfj GdQjGVj Ydi JaYjd GdMhGQ GdJQHhj cBdjI ddEJUGd GdJYdjej aj Xd GdJOQjS HGdebGQHI HGdcaGAGJ (B: (3ebGQHI JJeMhQ Mhd HYO GdfaS GdJQHhjs - (3WHdGhj, aGJMs; (3dYHGf, cQjes; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2018)
(3gOaJ GdOQGSI(B: (3Edi eMGhdI GdJYQa Ydi WHjYI GdYdGbI GdGQJHGWjI aj egGQGJ GdGJUGd eG Hjf GdeYde hGdeJYde CKfGA eeGQSI GdfTGW GdHOfj GdQjGVj, hGfYcGSgG Ydi GdJOQjS HGdebGQHI HGdcaGAGJ ef MjK GdLfS, hGdNHQI GdegfjI, hGdeSJhi GdCcGOjej, eY EecGfjI GdJMUjd GddZhj hJWhjQ GdeYGQa hegGQGJ GdGJUGd, chfg YedjI VQhQjI hgGeI dcd YedjGJ GdJhGab hGdage, hgPG HZQV GdhUhd Edi JMbjb GdCgOGa GdefThOI aj GdYedjI GdJQHhjI(B. (3CLQjJ GdOQGSI Ydi YjfI bhGegG (B24 (3CSJGP, h(B400(3JdejPG HeQMdI GdJYdje GdKGfhj dhdGjI GdeOjI, Je GNJjGQge HWQjbI YThGFjI efJXeI, hdLeY GdHjGfGJ GdNGUI HGdOQGSI, hddJMbb ef CgOGagG Je GSJNOGe GdefgL GdhUaj, dCfg edGFe hWHjYI GdehVhY(B. (3dcf ajeG jNU COhGJ LeY GdHjGfGJ GSJfOfG Edi GdcJH hGdeQGLY HGddZI GdYQHjI hGdaQfSjI, HGdEVGaI Edi GSJNOGe GdGSJHjGf, MjK Je HfGA abQGJg, GfWdGbG ef GdaQVjI heDTQGJgG, fGgjc Yf GSJNOGefG CjVG debjGS egGQGJ GdGJUGd GdehLg Edi cd ef GdCSGJPI hcPG GdJdGejP HUhQJjg C hH MjK jMJhj Ydi (B15 (3YHGQI aj cd UhQI, Je JUejeg ef WQa GdHGMK eMeO MSf YdGhj, CeG Yf GdCOGI GdKGdKI dbO GSJNOefG THcI GdedGMXI dYGde GdJQHjI GdCeQjcj adGfOQR GdNGUI HedGMXI GdJaGYd Ch GdGJUGd GddaXj eG Hjf GdeYde hGdeJYde, hGdJj JYJHQ chSjdI JZPjI QGLYI(B. (3hbO Je JfXje GdHjGfGJ hOQGSJgG HGSJYeGd HQfGeL GdMRe GdGMUGFjI (Bspss (3EP Je GdJhUd Edi GdfJGFL GdJGdjI(B: (3jSGge GdfTGW GdHOfj GdQjGVj aj JaYjd egGQGJ GdMhGQ GdGJUGdj eG Hjf GdeYde hGdeJYde CKfGA GdYedjI GdJYdjejI GdJYdejI aj Xd GdJOQjS HGdebGQHI HGdcaGAGJ(B. (3JhLO YdGbI EQJHGWjI aj egGQGJ GdGJUGd eG Hjf GdeYde hGdeJYde CKfGA eeGQSI GdfTGW GdHOfj GdQjGVj JfYcS Ydi GdJOQjS HGdebGQHI HGdcaGAGJ ef MjK GdLfS, GdNHQI GdegfjI, hGdeSJhi GdCcGOjej(B. (3JhLO aQhb PGJ OdGdI EMUGFjI aj egGQGJ GdGJUGd eG Hjf GdeYde hGdeJYde CKfGA GdYedjI GdJYdjejI GdJYdejI JfYcS Ydi GdJOQjS HGdebGQHI HGdcaGAGJ ef MjK WHjYI GdfTGW, hGdeSJhi GdOQGSj ddeJYdejf(B.s
(3GdOcJhQGgs
Keywords: (3GdEJUGd GdJYdjejs; (3GdJOQjS HGdebGQHI HGdcaGAGJ(B-s; (3GdfTGW GdHOfj GdQjGVj GdJQHhjs; (3GdfTGW GdHOfj GdQjGVjs